Extracellular Vesicles of Medicinal and Edible plants: Research Opportunities and Industrial Prospects of Natural Biological Carriers - Mei Zhou (Journal of Alternative, Complementary & Integrative Medicine, 2026)
In recent years, extracellular vesicles (EVs), as novel nanoscale biological carriers, mediating information exchange and material transport between cells, have become a research trend in the fields of life sciences basic medicine and biomedicine